Lateral Mandibular Incisor Impacted: First Case Report and Literature Review - Lorz Ulloa DDS, Patricia; Castro Fuentes DDS, Fabián; Mantilla Castro DDS, Luisa Fernanda (Odovtos - International Journal of Dental Sciences, 2016)
The presence of a lateral mandibular impacted tooth is quite strange. In the systematic literature review no other cases observed with the same characteristics. Is reported the case of a patient of 16 years with the left mandibular lateral tooth impacted near the apexes of adjacent teeth, which is decided to remove using the surgical technique of labial approach.